2014
DOI: 10.2308/acch-50810
|View full text |Cite
|
Sign up to set email alerts
|

CEO Origin and Accrual-Based Earnings Management

Abstract: SYNOPSIS This study examines the influence of CEO origin on accrual-based earnings management and how these effects evolve over the CEO's tenure in office. Compared with CEOs promoted from within the company, CEOs recruited from outside have a stronger incentive to demonstrate their abilities in the initial years after their appointment; these outside CEOs also may have a lower expectation of surviving the short run. We predict and find that outside CEOs engage in greater income-increasing manip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 39 publications
4
32
0
7
Order By: Relevance
“…In general, we found less evidence of omission and concealment and greater clarity and prominence of reporting with respect to target failure in such instances. We note that it is well documented that the manipulation of earnings must reverse over time (Kuang et al 2014, Marinovic 2014 and so is a short-term tactic that will be revealed over multiple accounting periods (Scott 2012). Effectively, over time managers will 'run out of ways to manage earnings' (Perols and Lougee 2011, p. 39) as they 'cannot indefinitely postpone the day of reckoning' (Scott 2012, p. 424).…”
mentioning
confidence: 84%
“…In general, we found less evidence of omission and concealment and greater clarity and prominence of reporting with respect to target failure in such instances. We note that it is well documented that the manipulation of earnings must reverse over time (Kuang et al 2014, Marinovic 2014 and so is a short-term tactic that will be revealed over multiple accounting periods (Scott 2012). Effectively, over time managers will 'run out of ways to manage earnings' (Perols and Lougee 2011, p. 39) as they 'cannot indefinitely postpone the day of reckoning' (Scott 2012, p. 424).…”
mentioning
confidence: 84%
“…Because the market and board heavily rely on current performance to evaluate a new CEO, and because even a competent CEO may lose his/her opportunity as his/her first performance was insufficient, a new CEO has an incentive to boost his/her performance in the early stage of tenure [8]. According to Kuang et al [31], because CEOs just hired outside the company have more incentive to prove their abilities while having less expectation to survive, they increase earnings in the early years of their tenure until they attain enough of a reputation to quit their short-term perspective. Because earnings manipulation is negatively related to corporate social performance [32][33][34], we may expect that the CSR level will be low at the early stage of CEO tenure.…”
Section: Hypothesismentioning
confidence: 99%
“… Other recent studies also use CEO tenure to capture career concerns in the context of managers' risk‐taking (Chen and Zheng ), pay‐performance sensitivity (Cremers and Palia ), earnings quality (Zhang ), and earnings management (Kuang, Qin, and Wielhouwer ). While one could consider CEOs' biological age as an alternative proxy for career concerns, we believe that age does not fully delineate the disparate disclosure incentives arising from concerns about ability assessments.…”
mentioning
confidence: 99%